High sperm DNA fragmentation delays human embryo kinetics when oocytes from young and healthy donors are microinjected. (26th September 2018) - Esbert, M.; Pacheco, A.; Soares, S. R.; Amorós, D.; Florensa, M.; Ballesteros, A.; Meseguer, M.
Abstract: Background: Time‐lapse monitoring (TLM) technology has been implemented in the clinical setting for the culture and selection of human embryos. Many studies have assessed the association between sperm DNA fragmentation (sDNAf) and clinical outcomes after ART, but little is known about the influence of sDNA on embryo morphokinetics. Objectives: The objective of this retrospective study, which includes 971 embryos from 135 consecutive ICSI cycles (56 cases with own oocytes, 79 with oocytes from young and healthy donors), was to assess if sDNAf has an impact on embryo morphokinetics. Materials and methods: Samples used to perform ICSI were analyzed by the flow cytometry TUNEL assay, and embryo development was assessed through an EmbyoScope ® system. The association between sDNAf and the timings of cell cleavage was analyzed by categorizing the first variable into quartiles: ≤6.50%; 6.51–10.70%; 10.71–20.15%; >20.15%. Results: In cases where sDNAf was above 20.15% (the upper quartile), embryos derived from donated oocytes ( n  = 644) showed significantly slower divisions. Such association was not observed in embryos obtained from the patients' own oocytes ( n  = 327). The embryo cleavage pattern (either normal, direct from 1 to 3 blastomeres, direct from 1 to 4 blastomeres, incomplete, reversed or asynchronous) was independent of the sDNAf level. Blastocyst arrival rate was 63.0% and the rate of good quality embryos (transferred and frozen embryos divided by the number of zygotes) was 45.49%. Neither parameter was related to the levels of sDNAf. Discussion: According to our results, the association between high sDNAf and donated oocytes led to delayed cell division. To our knowledge, this is the first study suggesting that sDNAf can delay human embryo cleavage timings when oocytes from donors are inseminated. Conclusions: This finding may indicate that, in the presence of increased DNA damage, time is needed before the first embryonic cell division for the activation of the optimal DNA repairing machinery in higher quality oocytes.